(untitled) (Academicia Globe: Inderscience Research, 2023)
This article details the modeling of intercultural communication discourse, the formation of an individual’s own culture through language learning, the purpose of studying a foreign language in conjunction with culture, and the positive and negative effects of intercultural communication on an individual.